Innovations in Derivatives Markets: Fixed Income Modeling, Valuation Adjustments, Risk Management, and Regulation - Glau, Kathrin; Grbac, Zorana; Scherer, Matthias; Zagst, Rudi (Springer Proceedings in Mathematics & Statistics, 2016)
Quantitative Finance; Banking; Statistics for Business/Economics/Mathematical Finance/Insurance; Mathematical Modelling and Industrial Mathematics; Probability Theory and Stochastic Processes; Financial Engineering